When You Put It that Way: Framing Gender Equality Initiatives to Improve Engagement among STEM Academics. (2nd December 2020) - Farrell, Lynn; Petzel, Zachary W; McCormack, Teresa; Turner, Rhiannon N; Rafferty, Karen; Latu, Ioana M
Abstract: A number of high-profile gender equality initiatives (GEIs) are intended to address women's underrepresentation in science. However, attitudes toward such initiatives can be negative. In two experiments with STEM academics, we examined how GEIs can be best framed to improve attitudes toward them. In study 1 ( N = 113), we manipulated the framing of GEI leadership (led by a man or woman) and GEI focus (benefitting men and women or benefitting women only). The men were more supportive of GEIs benefitting both men and women because of fewer concerns of unfair treatment and more internal motivations to engage with GEIs. The women's level of support was unaffected by framing. In study 2 ( N = 151), we framed GEIs as either supported by university management or not and either internally or externally driven. Support was greater for internally driven GEIs. The impact of management support depended on the academics' experience with GEIs. This research makes evidence-based recommendations for the implementation of GEIs to improve their effectiveness.